Impact of Mast Cells in Rejection of Allografts. (September 2013) - Kritas, S.K.; Saggini, A.; Varvara, G.; Murmura, G.; Caraffa, A.; Antinolfi, P.; Tomato, E.; Pantalone, A.; Neri, G.; Frydas, S.; Rosati, M.; Tei, M.; et al.
Mast cells in the tissue are located close to nerves in and around the small vessels where they orchestrate important immune response after antigen recognition through Toll-like receptors. Mast cells can activate T and B lymphocytes and dendritic cells and have been postulated to act directly within tissue allografts and/or to induce indirect effects via inflammatory mediator release, therefore they have been shown to play an indispensable role in allograft tolerance. Major limitation in the success of transplantation is the immune response of the recipient to the donor tissue. The failure of tissue grafting is caused by an inflammatory reaction called rejection. Mast cells play a role during immune response and are elicited with transplanted allograft and also may exhibit their immune-regulatory effects directly through secretion of modulatory cytokines and activation of metabolic pathways. However, the role of mast cells in transplantation is poorly understood. The most severe rejection episodes have been found in patients with an increased number of mast cells. Mast cell mediators which can activate latent forms of TGF-β or increase angiotensin II levels are capable of inducing fibrosis through various mechanisms, activating fibroblasts and inducing collagen synthesis. Mast cells are also implicated in regulatory T-cell functions and are required to sustain peripheral tolerance via Treg, therefore there is an interaction between mast cells and Treg cells. Treg create IL-9 in enhancing mast cell growth and Chemotaxis, suggesting that Treg and mast cells form a functional unit that mediates graft tolerance. In this study we concentrate our attention on the role of mast cells in rejection of allografts and try to understand the role of mast cell-related immune mechanisms in organ transplantation.